The problem of archaeological study of the final stage of Hittite Kingdom history: Historiographical aspect - A. I. Mishchenko (Шаги)
The purpose of this research is to study and systemize foreign and Russian literature on key Hittite settlements in terms of the problem of the crisis of the Hittite Kingdom at the turn of the 13th–12th centuries B. C. Due to a lack of generalizing historiographical summaries on this issue in modern Russian scholarship, as well as in view of the large number of new archaeological data that have appeared since the early 2000s as a result of modern archaeological excavations in Turkey, there appeared a real need for analysis of the latest materials, thanks to which a new outlook on the phenomenon of the decline of the Late Bronze Age civilization of Anatolia is possible. The main sources of this study consist primarily of archaeological surveys and excavation reports from Hittite settlements in Central Anatolia, articles from academic journals and research series and monographs. The analyzed data made it possible to identify several stages in the development of historiography and to show the need for a gradual correlation of new archaeological materials from settlements in Central Anatolia with known written sources in order to reach a more comprehensive understanding of the events of the Late Bronze Age and the Early Iron Age in Anatolia.